Employee silence and voice : an empirical study of potential antecedents and the moderating role of employee conscientiousness - Abdulla, Fathmath Najadha (My University, 2021)
ABSTRACTEMPLOYEE SILENCE AND VOICE:AN EMPIRICAL STUDY OF POTENTIAL ANTECEDENTS AND THE MODERATING ROLE OF EMPLOYEE CONSCIENTIOUSNESSTo achieve its goals, flow of information and communication between employees and departments is strategic to every organization. A more open working environment is only possible when there is free flow of information with no obstructions. However, organizational progress is often affected when employees decide to remain silent and refrain from expressing their opinions and concerns.The main aim of this study is to identify whether employee silence exists among the sample group of employees in the Maldives and identify the reasons why employees remain silent. This study consists of both qualitative and quantitative methods. First, factors contributing to employee silence/ voice are identified by conducting face to face interviews with ten employees who work in various public organizations in the Maldives. The results indicated that the most repeated antecedents of silence/ voice are; perceived interactional justice, trust in management, perceived job security, and perception of organizational politics. The results of this exploratory study also point to the existence of employee silence among the sample group in the Maldives. Second, the most repeated antecedents of silence/ voice are used to develop the research model and test their contribution to employee voice/ silence. In addition, the moderating role of employee conscientiousness is tested in the voice construct. For this part of the study, convenient sampling is used with a sample size of 422 employees working in public organizations. The results indicate that perceived interactional justice and perceived job security positively contribute to employee voice, and perception of organizational politics positively contributes to employee silence. The moderating effect of employee conscientiousness is not significant.

ABSTRACTEMPLOYEE SILENCE AND VOICE:AN EMPIRICAL STUDY OF POTENTIAL ANTECEDENTS AND THE MODERATING ROLE OF EMPLOYEE CONSCIENTIOUSNESSTo achieve its goals, flow of information and communication between employees and departments is strategic to every organization. A more open working environment is only possible when there is free flow of information with no obstructions. However, organizational progress is often affected when employees decide to remain silent and refrain from expressing their opinions and concerns.The main aim of this study is to identify whether employee silence exists among the sample group of employees in the Maldives and identify the reasons why employees remain silent. This study consists of both qualitative and quantitative methods. First, factors contributing to employee silence/ voice are identified by conducting face to face interviews with ten employees who work in various public organizations in the Maldives. The results indicated that the most repeated antecedents of silence/ voice are; perceived interactional justice, trust in management, perceived job security, and perception of organizational politics. The results of this exploratory study also point to the existence of employee silence among the sample group in the Maldives. Second, the most repeated antecedents of silence/ voice are used to develop the research model and test their contribution to employee voice/ silence. In addition, the moderating role of employee conscientiousness is tested in the voice construct. For this part of the study, convenient sampling is used with a sample size of 422 employees working in public organizations. The results indicate that perceived interactional justice and perceived job security positively contribute to employee voice, and perception of organizational politics positively contributes to employee silence. The moderating effect of employee conscientiousness is not significant.
Keywords: Business; employee conscientiousness; employee conscientiousness employee silence/ voice; employee silence/ voice; İşletme; perceived interactional justice; perceived job security; perception of organizational politics; trust in management